Quality improvement programme to increase the rate of deferred cord clamping at preterm birth using the Lifestart trolley. Issue 6 (29th April 2020) - Hoyle, Emily Suzanne; Hirani, Sunaya; Ogden, Sally; Deeming, Jenna; Yoxall, Charles William
Abstract : Aim: To increase the documented use of the Lifestart trolley to allow premature infants' (<32 weeks' gestation) resuscitation and stabilisation with an intact umbilical cord at delivery. Design: A 13-month quality improvement programme from April 2018 to April 2019 was undertaken using Plan, Do, Study and Act (PDSA) cycles. Data were reviewed from 113 consecutive preterm (<32 weeks) deliveries to identify whether Lifestart was used and whether 2 min deferred cord clamping (DCC) occurred in eligible infants as per hospital policy. Episodes of non-compliance were analysed, causes established and interventions implemented to reduce similar future non-compliance. Data collected were presented graphically and included in alternate monthly newsletters to staff, which also included lessons learnt from the reviews of non-compliance. Results: Documented use of the Lifestart rose from 10% at the start of the project to 79% in the final month. Not all babies are eligible for DCC. Within this project, 40 (35%) of preterm infants were not eligible to receive DCC. Of those that were eligible, the rate of DCC increased from 17% in the first 3 months to 92% in the last 3 months of the project (p<0.0001). Implications and relevance: By undertaking regular PDSA cycles and improving education surrounding importance of DCC, we have noted a significant improvement in the use of Lifestart, which in turn facilitates DCC. The learning from this project has been used to create an instructional video to help maintain the improved compliance rates.